2015
DOI: 10.3892/ijo.2015.2933
|View full text |Cite
|
Sign up to set email alerts
|

CecropinXJ inhibits the proliferation of human gastric cancer BGC823 cells and induces cell death in vitro and in vivo

Abstract: Abstract. We have shown that an antimicrobial peptide (AMP) cecropinXJ isolated from the larvae of Bombyx mori selectively inhibits the proliferation of cancer cells. However, the mechanism remains to be determined. In the present study, we examined the antitumor activity of cecropinXJ against human gastric cancer BGC823 cells and explored the mechanism. The results showed that cecropinXJ inhibited the growth of gastric cancer BGC823 cells in vitro and in vivo. MTT and colony formation assays indicated that ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…CecropinXJ may effectively inhibit the proliferation of human gastric cancer BGC823 cells ( 12 ). Studies investigating the effect of cecropinXJ on the growth of malignant ascites tumors are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CecropinXJ may effectively inhibit the proliferation of human gastric cancer BGC823 cells ( 12 ). Studies investigating the effect of cecropinXJ on the growth of malignant ascites tumors are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…CecropinXJ demonstrates a broad activity against bacteria and fungi ( 10 , 11 ). Previous studies have revealed that cecropinXJ may inhibit the proliferation of human BGC823 gastric cancer cells in vitro ( 12 ), whereas, it demonstrates no hemolytic effects against human erythrocytes and no toxicity to healthy mammalian cells ( 13 , 14 ). However, to the best of the author's knowledge, no relevant studies have been performed to date that explore the effects of cecropinXJ on the growth of tumor-associated ascites in human gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Over-activated Akt achieves its anti-apoptotic effects by phosphorylating various substrates such as Bad (39) and caspase-9 (40). Previous studies have revealed that cecropinXJ may inhibit Bad phosphorylation (16,17). p-Bad may combine with Bcl-2 or Bcl-XL on the mitochondrial membrane to prevent the release of cytochrome c from the mitochondria and the activation of caspase-9 (41).…”
Section: Discussionmentioning
confidence: 99%
“…CecropinXJ elicits a broad spectrum of effects against bacteria and fungi (14,15). Our previous studies indicated that cecropinXJ exhibits anti-tumor and anti-proliferation activities, and an apoptosis-promoting effect on human gastric cancer AGS (16), and BGC823 cells (17). In addition, apoptosis is mediated by the Combination of cecropinXJ and LY294002 induces synergistic cytotoxicity, and apoptosis in human gastric cancer cells via inhibition of the PI3K/Akt signaling pathway mitochondrial apoptotic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…ROS production increase and mitochondrial membrane potential (m) disruption induced by several natural compounds have been associated to the growth inhibition of different cancer models [12][13][14]. Then, T24 cells were treated with 20 µM NDGA for 2 to 72 h and m ( Figure 2A) and ROS production ( Figure 2B) were evaluated.…”
mentioning
confidence: 99%